Relasi Religiusitas dengan Bonum Commune: Tinjauan Kritis terhadap Implikasi Religiusitas Jamaah Dzikir Hizb Nashr di Pondok Pesantren An Nuriyah Kaliwining Jember: The Relation Between Religiosity and Bonum Commune: A Critical Review of the Implications of Religiosity Among the Dzikir Hizb Nashr Congregation at An Nuriyah Islamic Boarding School, Kaliwining Jember - Usuluddin, Win (Fenomena, 2011)
The focus of this research was the social implications for the members of Dzikir Hizbun Nashr at An Nuriyah Islamic Boarding School, Kaliwining Jember. These implications are important to describe religion as both individual subjectivity and general community objectivity, as portrayed in the routine activities of the Dzikir Hizbun Nashr followers at An Nuriyah Islamic Boarding School, Kaliwining Jember. The research aimed to provide an adequate descriptive explanation of the problem, ultimately answering the research question of how this activity contributes to the creation of bonum commune for the Dzikir Hizbun Nashr followers at An Nuriyah Islamic Boarding School, Kaliwining Jember. Essentially, it is hoped that this research will contribute to the discourse on the relationship between faith and bonum commune, particularly Aristotle's concept of bonum commune. The research method employed was descriptive, holistic, hermeneutic, and critical reflection. The findings indicate that religion serves as both individual subjectivity and general objectivity, which can lead to the creation of bonum commune for the Dzikir Hizbun Nashr followers at An Nuriyah Islamic Boarding School, Kaliwining Jember. Fokus penelitian ini adalah implikasi sosial terhadap anggota Dzikir Hizbun Nashr di Pondok Pesantren An Nuriyah Kaliwining Jember. Implikasi tersebut penting untuk menggambarkan agama sebagai subjektivitas individu sekaligus objektivitas umum komunitas, sebagaimana tergambar dalam aktivitas rutin para pengikut Dzikir Hizbun Nashr di Pondok Pesantren An Nuriyah Kaliwining Jember. Tujuan penelitian adalah untuk mendapatkan deskripsi yang memadai mengenai masalah tersebut, sehingga dapat menjawab pertanyaan penelitian tentang bagaimana aktivitas ini berkontribusi pada penciptaan bonum commune bagi para pengikut Dzikir Hizbun Nashr di Pondok Pesantren An Nuriyah Kaliwining Jember. Pada dasarnya, diharapkan temuan penelitian ini dapat memperkaya pemikiran tentang relasi antara keimanan dan bonum commune, dalam hal ini bonum commune versi Aristoteles. Metode penelitian yang digunakan adalah deskriptif, holistik, hermeneutik, dan refleksi kritis. Hasil penelitian menunjukkan bahwa agama merupakan subjektivitas individu sekaligus objektivitas umum yang dapat mengarah pada penciptaan bonum commune bagi para pengikut Dzikir Hizbun Nashr di Pondok Pesantren An Nuriyah Kaliwining Jember.